Low smoke halogen-free flame retardant cable for subway
By adding organic modified boron fibers to the materials of low-smoke halogen-free flame retardant cables for subways and performing specific grafting treatment, the problem of the decrease in tensile strength after the addition of flame retardant is solved, and higher tensile strength and flame retardant are achieved, which extends the service life and improves the fire treatment effect.
Patent Information
- Application Number
- CN202411975295.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The existing low-smoke halogen-free flame retardant cables for subway use decrease in tensile strength after adding flame retardant, affecting their service life.
Low-smoke, halogen-free flame-retardant polyolefin material consisting of ethylene-vinyl acetate copolymer, metallocene polyethylene, maleic anhydride grafted polyethylene, triglycidyl isocyanurate, organic modified boron fibers, lubricants, antioxidants and flame retardant, and the tensile strength and flame retardant of the material are improved by grafting specific organic matter on the surface of the boron fiber.
It significantly improves the tensile strength, notch impact strength and limit oxygen index of low-smoke halogen-free flame retardant cables, extends the service life, slows down the combustion speed during fire, inhibits the spread of flames, has less smoke, less harmful gas release, and low smoke toxicity.
Smart Images

Figure CN119381067B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of cable technology, and more specifically, to a low-smoke, halogen-free, flame-retardant cable for subways. Background Art
[0002] Cables are carriers for power and communication transmission and have been widely used in industries such as subways, aerospace, ships, construction, petrochemicals, and steel smelting. When cables are used in subways, the flame retardancy of cables has become one of the important considerations that are indispensable in rail transit systems. The existing subway cables often use low-smoke halogen-free flame-retardant cables. Low-smoke halogen-free flame-retardant cables generally include cable cores, the number of which can be set to one, two, or more as needed, the outer circumference of the cable core is provided with a sheath layer, and the outer circumference of the sheath layer is provided with a sheath layer, which is made of low-smoke halogen-free flame-retardant polyolefin materials. In order to make low-smoke halogen-free flame-retardant polyolefin materials have good flame retardancy, flame retardants such as magnesium hydroxide or aluminum hydroxide are often added to ethylene-vinyl acetate copolymers to slow down the burning speed and inhibit the spread of flames. However, the applicant found in actual research that adding flame retardants to ethylene-vinyl acetate copolymers, although the flame retardancy is improved, leads to a decrease in tensile strength, which affects the service life of low-smoke halogen-free flame-retardant cables. Summary of the invention
[0003] In order to improve the tensile strength of low-smoke halogen-free flame-retardant polyolefin materials, thereby increasing the service life of low-smoke halogen-free flame-retardant cables, the present application provides a low-smoke halogen-free flame-retardant cable for subways, which adopts the following technical solutions:
[0004] Low-smoke halogen-free flame-retardant cable for subway, the low-smoke halogen-free flame-retardant cable comprises a plurality of cable cores, the outer circumference of the plurality of cable cores is provided with a wrapping layer, a filler is provided between the wrapping layer and the cable core, and the outer circumference of the wrapping layer is provided with an inner protective layer, a ceramic silicone layer, a metal braided layer, and a sheath layer in sequence from inside to outside; the sheath layer is made of low-smoke halogen-free flame-retardant polyolefin material;
[0005] The low-smoke halogen-free flame-retardant polyolefin material is mainly made of the following raw materials in parts by weight: 60-80 parts of ethylene-vinyl acetate copolymer, 20-40 parts of metallocene polyethylene, 10-20 parts of maleic anhydride grafted polyethylene, 2-4 parts of triglycidyl isocyanurate, 4-6 parts of organically modified boron fiber, 1-3 parts of lubricant, 1-3 parts of antioxidant, and 70-90 parts of flame retardant; the organically modified boron fiber is obtained by treating boron fiber with 3-(methacryloyloxy)propyltrimethoxysilane, triallyl isocyanurate, diethylene glycol monoallyl ether, and sucrose oleate.
[0006] The low-smoke halogen-free flame-retardant cable for subways of the present application is rounded and compacted through the cooperation between various structures, and the inner protective layer, ceramic silicone layer, metal braided layer, and sheath layer are sequentially arranged on the outer peripheral surface of the sheath layer to enhance the overall mechanical strength and fire and moisture resistance of the low-smoke halogen-free flame-retardant cable. In addition, when a fire occurs, it can slow down the burning speed and inhibit the spread of flames. In addition, the amount of smoke during the combustion process is small, the release of harmful gases is small, the toxicity of smoke is low, the impact on the environment is reduced, and it is also conducive to the safety of personnel escape and rescue.
[0007] The low-smoke, halogen-free, flame-retardant polyolefin material of the present application has a tensile strength of >27MPa and a notched impact strength of >21kJ / m through the mutual coordination of the raw materials. 2 , limiting oxygen index > 35%, which makes the low-smoke halogen-free flame-retardant polyolefin material show the advantages of high tensile strength, high notch impact strength, large limiting oxygen index and high flame retardancy. It has better comprehensive performance and can be used in subway low-smoke halogen-free flame-retardant cables to meet market demand.
[0008] The high temperature and wear resistant cable material of the present application is based on ethylene-vinyl acetate copolymer and metallocene polyethylene. On this basis, organic modified boron fiber is added, and 3-(methacryloyloxy)propyltrimethoxysilane, triallyl isocyanurate, diethylene glycol monoallyl ether, and sucrose oleate are grafted on the surface of the boron fiber. Active groups such as siloxy, ester, isocyanurate, ether, and hydroxyl groups are introduced, and the number of branches is increased, the grafting density is improved, the dispersibility, compatibility, and bonding strength are increased, the stability of the three-dimensional network structure is enhanced, the structural defects are reduced, the strength and flame retardancy are improved, and the low-smoke halogen-free flame retardant polyolefin material exhibits better tensile strength, notched impact strength, and limiting oxygen index, thereby extending the use stability and life, and improving safety and reliability.
[0009] Optionally, the organic modified boron fiber is prepared by the following method:
[0010] T1. Mix water and sodium hydroxide, add boron fiber, stir for 1-3 hours, filter, and obtain pretreated boron fiber;
[0011] T2, mixing water and pretreated boron fiber, adding 3-(methacryloyloxy)propyltrimethoxysilane, stirring for 2-4 hours, filtering, and obtaining a grafted boron fiber intermediate;
[0012] T3. Mix isopropanol and toluene, add the grafted boron fiber intermediate, add triallyl isocyanurate, diethylene glycol monoallyl ether, and sucrose oleate, add an organic initiator, stir for 2-4 hours, filter, wash, and dry to obtain organically modified boron fiber.
[0013] Optionally, the weight ratio of the boron fiber, 3-(methacryloyloxy)propyltrimethoxysilane, triallyl isocyanurate, diethylene glycol monoallyl ether, and sucrose oleate is (9-11):(1-3):(0.5-1.5):(1-3):(1-3).
[0014] By adopting the above technical scheme, the boron fiber is first activated with sodium hydroxide to improve the activity of the boron fiber, increase the active sites on the surface of the boron fiber, and obtain the pretreated boron fiber. Then, 3-(methacryloyloxy)propyltrimethoxysilane is grafted on the surface of the pretreated boron fiber to obtain a grafted boron fiber intermediate, and a siloxy group, an ester group, and a carbon-carbon double bond are introduced. After that, by using the polymerization reaction of the carbon-carbon double bond, triallyl isocyanurate, diethylene glycol monoallyl ether, and sucrose oleate are grafted on the surface of the grafted boron fiber intermediate to obtain an organically modified boron fiber, and isocyanurate, ether group, hydroxyl group, etc. are introduced. At the same time, because triallyl isocyanurate contains three carbon-carbon double bonds, and the carbon-carbon double bond in sucrose oleate is located in the middle position, the number of side chains is increased. The organically modified boron fiber obtained by the preparation method of the present application improves the grafting density, improves the dispersibility, compatibility and bonding strength, improves the tensile strength, notched impact strength and limiting oxygen index, so that the low-smoke halogen-free flame-retardant polyolefin material exhibits better comprehensive performance.
[0015] Optionally, in step T1, the weight ratio of the boron fiber, water and sodium hydroxide is (9-11):(40-60):(4-6).
[0016] By adopting the above technical scheme, the addition amount of water and sodium hydroxide is optimized, which is convenient for full contact and reaction of the raw materials, fully activates the boron fiber, facilitates the grafting treatment of the pretreated boron fiber, and further ensures the stability and quality of the preparation of the organic modified boron fiber.
[0017] Optionally, in step T2, the weight ratio of 3-(methacryloyloxy)propyltrimethoxysilane and water is (1-3):(80-120).
[0018] By adopting the above technical solution, the amount of water added is optimized, which facilitates the full contact and reaction of the pretreated boron fiber and 3-(methacryloyloxy)propyltrimethoxysilane, and can also ensure the stability of the reaction system and the stability of the preparation of the grafted boron fiber intermediate.
[0019] Optionally, in step T3, the weight ratio of triallyl isocyanurate, isopropanol and toluene is (0.5-1.5):(60-80):(20-40).
[0020] By adopting the above technical scheme, the addition amount of isopropanol and toluene is optimized, which facilitates the full contact and reaction of the raw materials, ensures the stability of the reaction system, reduces the occurrence of side reactions, and ensures the stability and use effect of the preparation of organic modified boron fiber.
[0021] Optionally, the organic initiator is one or more of benzoyl peroxide, tert-butyl perbenzoate, cumene hydroperoxide, and tert-butyl hydroperoxide.
[0022] By adopting the above technical solution, the organic initiator is optimized, which facilitates the selection of the organic initiator. The organic initiator can release free radicals and promote polymerization reaction to achieve the grafting of triallyl isocyanurate, diethylene glycol monoallyl ether, and sucrose oleate.
[0023] Optionally, the boron fibers have an average diameter of 30-300 μm and an average length of 1-5 mm.
[0024] By adopting the above technical solution, the average diameter and average length of the boron fiber are optimized, thereby achieving the optimization of the average diameter and average length of the organic modified boron fiber, making the organic modified boron fiber uniformly dispersed in the raw material, enhancing the structural stability of the low-smoke halogen-free flame-retardant polyolefin material, and improving the strength and flame retardancy. In multiple implementation schemes, the average diameter of the carbon core boron fiber is 100 μm and the average length is 2 mm. The average diameter can also be set to 30 μm, 50 μm, 80 μm, 130 μm, 150 μm, 180 μm, 200 μm, 230 μm, 250 μm, 280 μm, 300 μm as needed, and the average length can also be set to 1 mm, 3 mm, 4 mm, 5 mm as needed, but it is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0025] Optionally, the lubricant is one or more of stearic acid, zinc stearate, stearic acid amide, and ethylene bis stearic acid amide.
[0026] By adopting the above technical solution, the lubricant is optimized, which is convenient for the selection of lubricants. The lubricant can reduce friction, reduce adhesion, improve the processability of low-smoke halogen-free flame-retardant polyolefin materials, and ensure the quality of low-smoke halogen-free flame-retardant polyolefin materials.
[0027] Optionally, the lubricant is ethylene bis stearic acid amide and zinc stearate, and the weight ratio of ethylene bis stearic acid amide and zinc stearate is (1-3): (1-3). In multiple embodiments, the weight ratio of ethylene bis stearic acid amide and zinc stearate is 2:1, and the weight ratio can also be set to 1:1, 1:2, 1:3, 2:3, 3:1, 3:2 as needed, but it is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0028] Optionally, the antioxidant is one or more of antioxidant 1010, antioxidant 1076, antioxidant 2246, antioxidant 168, and antioxidant TH-412S.
[0029] By adopting the above technical solution, the antioxidant is optimized and the selection of the antioxidant is facilitated. The antioxidant can effectively improve the antioxidant performance of the low-smoke halogen-free flame-retardant polyolefin material and extend the stability and life of use.
[0030] Optionally, the antioxidants are two kinds of antioxidants, namely, antioxidant 1010 and antioxidant 168, and the weight ratio of antioxidant 1010 to antioxidant 168 is (1-3):(1-3). In multiple embodiments, the weight ratio of antioxidant 1010 to antioxidant 168 is 1:2, and the weight ratio can also be set to 1:1, 1:3, 2:1, 2:3, 3:1, 3:2 as needed, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0031] Optionally, the flame retardant is one or more of magnesium hydroxide, aluminum hydroxide, and zinc borate.
[0032] By adopting the above technical solution, the flame retardant is optimized, which facilitates the selection of flame retardants. Flame retardants can decompose at high temperatures, absorb a large amount of heat, and reduce the combustion temperature. The decomposed products can cover the surface of the burning object and form a dense protective layer, which plays a role in heat insulation and oxygen isolation to prevent combustion. At the same time, dehydration reaction can occur and release water vapor to dilute the concentration of combustible gas, weaken the combustion reaction, further prevent combustion, and improve the flame retardant effect.
[0033] Optionally, the flame retardant is magnesium hydroxide and aluminum hydroxide, and the weight ratio of magnesium hydroxide to aluminum hydroxide is (1-3): (1-3). In multiple embodiments, the weight ratio of magnesium hydroxide to aluminum hydroxide is 1:2, and the weight ratio can also be set to 1:1, 1:3, 2:1, 2:3, 3:1, 3:2 as needed, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0034] Optionally, the mass content of vinyl acetate in the ethylene-vinyl acetate copolymer is 12-24%, and the melt index is 1-5 g / 10 min. In multiple embodiments, the mass content of vinyl acetate in the ethylene-vinyl acetate copolymer is 18%, and the melt index is 2.5 g / 10 min. The mass content can also be set to 12%, 15%, 20%, 24% as required, and the melt index can also be set to 1 g / 10 min, 2 g / 10 min, 3 g / 10 min, 4 g / 10 min, 5 g / 10 min as required, but it is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0035] Optionally, the density of the metallocene polyethylene is 0.85-0.98 g / cm 3 , melt index is 0.5-5g / 10min. In various embodiments, the density of the metallocene polyethylene is 0.94g / cm 3 The melt index is 1.2g / 10min, and the density can also be set to 0.85g / cm 3 , 0.88g / cm 3 , 0.90g / cm 3 , 0.95g / cm 3 、0.98g / cm 3 The melt index can also be set to 0.5g / 10min, 1g / 10min, 2g / 10min, 3g / 10min, 4g / 10min, 5g / 10min as needed, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0036] Optionally, the low-smoke halogen-free flame-retardant polyolefin material is prepared by the following method:
[0037] Ethylene-vinyl acetate copolymer, metallocene polyethylene, maleic anhydride grafted polyethylene, triglycidyl isocyanurate, organic modified boron fiber, lubricant, antioxidant and flame retardant are mixed and extruded into granules to obtain low-smoke halogen-free flame retardant polyolefin material.
[0038] By adopting the above technical solution, the preparation of low-smoke halogen-free flame-retardant polyolefin materials is facilitated.
[0039] Optionally, in the extrusion granulation process, a twin-screw extruder is used with an extrusion temperature of 150-170° C. and a rotation speed of 300-500 r / min.
[0040] By adopting the above technical solution, the extrusion temperature and rotation speed are optimized, the raw materials are fully mixed, the dispersion uniformity is enhanced, and the thermal degradation caused by excessive temperature is reduced, so as to ensure the stability of the preparation of low-smoke halogen-free flame-retardant polyolefin materials. In multiple implementation schemes, the extrusion temperature is 160°C and the rotation speed is 400r / min. The extrusion temperature can also be set to 150°C, 155°C, 165°C, and 170°C as needed. The rotation speed can also be set to 300r / min, 350r / min, 450r / min, and 500r / min as needed, but it is not limited to the listed values. Other values not listed in the numerical range are also applicable.
[0041] In summary, this application has at least the following beneficial effects:
[0042] 1. The low-smoke halogen-free flame-retardant cable for subways of this application enhances the overall mechanical strength and fire and moisture resistance of the low-smoke halogen-free flame-retardant cable through the mutual cooperation between various structures. In addition, in the event of a fire, it slows down the burning speed and inhibits the spread of the flame. It also has the characteristics of less smoke, less harmful gas release, and low smoke toxicity, which can reduce the impact on the environment and is also conducive to the safety of personnel escape and rescue;
[0043] 2. The low-smoke halogen-free flame-retardant polyolefin material of the present application adds organic modified boron fiber to the raw material, and uses 3-(methacryloyloxy)propyltrimethoxysilane, triallyl isocyanurate, diethylene glycol monoallyl ether, and sucrose oleate to treat the boron fiber, which significantly increases the dispersibility, compatibility and bonding strength, improves the stability of the three-dimensional network structure, reduces structural defects, and makes the low-smoke halogen-free flame-retardant polyolefin material show better tensile strength, notched impact strength and limiting oxygen index, with tensile strength>27MPa and notched impact strength>21kJ / m 2 , limiting oxygen index>35%, can be used in subway low-smoke halogen-free flame-retardant cables to meet market demand. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 It is a schematic cross-sectional view of the low-smoke halogen-free flame-retardant cable of Example 1 of the present application.
[0045] Explanation of the reference numerals: 1. cable core; 2. sheath; 3. filler; 4. inner sheath; 5. ceramic silicone layer; 6. metal braided layer; 7. sheath layer. DETAILED DESCRIPTION
[0046] In order to make the present application easier to understand, the present application will be further described in detail below in conjunction with the examples, which are merely illustrative and are not intended to limit the scope of application of the present application. The raw materials or components used in the present application can be obtained through commercial routes or conventional methods unless otherwise specified.
[0047] Preparation Example
[0048] Preparation Example 1
[0049] An organic modified boron fiber is prepared by the following method:
[0050] T1. Add 5 kg of sodium hydroxide to 50 kg of water at a rotation speed of 300 r / min, stir for 5 min, add 10 kg of boron fiber, stir for 2 h, filter, and obtain pretreated boron fiber.
[0051] The boron fiber is a carbon core boron fiber, and the average diameter of the carbon core boron fiber is 100 μm, the average length is 2 mm, and the tensile strength is 4 GPa.
[0052] T2. Add the pretreated boron fiber obtained in step T1 to 100 kg of water at a rotation speed of 300 r / min, stir for 5 min, add 2 kg of 3-(methacryloyloxy)propyltrimethoxysilane, stir for 3 h, filter, and obtain a grafted boron fiber intermediate.
[0053] T3. Add 30 kg of toluene to 70 kg of isopropanol at a speed of 300 r / min and stir for 5 min. Add the grafted boron fiber intermediate obtained in step T2 and stir for 5 min. Add 1 kg of triallyl isocyanurate, 2 kg of diethylene glycol monoallyl ether, and 2 kg of sucrose oleate and stir for 5 min. Add 0.1 kg of organic initiator and stir for 3 h, filter, wash, and dry to obtain organically modified boron fiber.
[0054] Among them, the organic initiator is benzoyl peroxide; in the washing treatment, it is washed once with 30 kg of ethanol, then washed once with 30 kg of ethanol aqueous solution with a mass concentration of 30%, and then washed once with 30 kg of water to complete the washing treatment.
[0055] Preparation Example 2
[0056] An organic modified boron fiber is prepared by the following method:
[0057] T1. Add 6 kg of sodium hydroxide to 40 kg of water at a rotation speed of 300 r / min, stir for 5 min, add 9 kg of boron fiber, stir for 1 h, filter, and obtain pretreated boron fiber.
[0058] The boron fiber is a carbon core boron fiber, and the average diameter of the carbon core boron fiber is 100 μm, the average length is 2 mm, and the tensile strength is 4 GPa.
[0059] T2. Add the pretreated boron fiber obtained in step T1 to 80 kg of water at a rotation speed of 300 r / min, stir for 5 min, add 1 kg of 3-(methacryloyloxy)propyltrimethoxysilane, stir for 2 h, filter, and obtain a grafted boron fiber intermediate.
[0060] T3, at a speed of 300r / min, add 40kg of toluene to 60kg of isopropanol and stir for 5min. Add the grafted boron fiber intermediate obtained in step T2 and stir for 5min. Add 0.5kg of triallyl isocyanurate, 3kg of diethylene glycol monoallyl ether, and 1kg of sucrose oleate and stir for 5min. Add 0.05kg of organic initiator and stir for 4h, filter, wash, and dry to obtain organic modified boron fiber.
[0061] Among them, the organic initiator is benzoyl peroxide; in the washing treatment, it is washed once with 30 kg of ethanol, then washed once with 30 kg of ethanol aqueous solution with a mass concentration of 30%, and then washed once with 30 kg of water to complete the washing treatment.
[0062] Preparation Example 3
[0063] An organic modified boron fiber is prepared by the following method:
[0064] T1. Add 4 kg of sodium hydroxide to 60 kg of water at a rotation speed of 300 r / min, stir for 5 min, add 11 kg of boron fiber, stir for 3 h, filter, and obtain pretreated boron fiber.
[0065] The boron fiber is a carbon core boron fiber, and the average diameter of the carbon core boron fiber is 100 μm, the average length is 2 mm, and the tensile strength is 4 GPa.
[0066] T2. Add the pretreated boron fiber obtained in step T1 to 120 kg of water at a rotation speed of 300 r / min, stir for 5 min, add 3 kg of 3-(methacryloyloxy)propyltrimethoxysilane, stir for 4 h, filter, and obtain a grafted boron fiber intermediate.
[0067] T3. Add 20 kg of toluene to 80 kg of isopropanol at a speed of 300 r / min and stir for 5 min. Add the grafted boron fiber intermediate obtained in step T2 and stir for 5 min. Add 1.5 kg of triallyl isocyanurate, 1 kg of diethylene glycol monoallyl ether, and 3 kg of sucrose oleate and stir for 5 min. Add 0.15 kg of an organic initiator and stir for 2 h, filter, wash, and dry to obtain an organically modified boron fiber.
[0068] Among them, the organic initiator is benzoyl peroxide; in the washing treatment, it is washed once with 30 kg of ethanol, then washed once with 30 kg of ethanol aqueous solution with a mass concentration of 30%, and then washed once with 30 kg of water to complete the washing treatment.
[0069] Example
[0070] Example 1
[0071] A low smoke halogen-free flame retardant cable for subway, refer to Figure 1 The low-smoke halogen-free flame-retardant cable includes three cable cores 1, and the cross-section of the cable core 1 is circular. The outer circumference of the three cable cores 1 is wrapped with a wrapping layer 2, which is a glass fiber tape and is double wrapped, and the repetition rate of each layer is 30%. The gap between the wrapping layer 2 and the three cable cores 1 is provided with a filler 3, which is a glass fiber rope. The filler 3 and the three cable cores 1 are cabled simultaneously, and during the cabling process, the outer circumference of the filler 3 is wrapped with a glass fiber tape to form a wrapping layer 2. Through the mutual cooperation between the cable core 1, the wrapping layer 2, and the filler 3, the overall cross-section is circular, and the roundness and tightness are guaranteed.
[0072] The outer circumference of the wrapping layer 2 is provided with an inner protective layer 4, which is made of low-smoke halogen-free flame-retardant polyolefin material through extrusion. The outer circumference of the inner protective layer 4 is provided with a ceramic silicone layer 5, which is a ceramic silicone tape and is formed by double wrapping, and the repetition rate of each layer of wrapping is 30%. The outer circumference of the ceramic silicone layer 5 is provided with a metal braided layer 6, which is an aluminum wire braided mesh, which is woven with aluminum wire and has a braiding density of 80%. The outer circumference of the metal braided layer 6 is provided with a sheath layer 7, which is made of low-smoke halogen-free flame-retardant polyolefin material through extrusion.
[0073] Among them, the low-smoke halogen-free flame-retardant polyolefin material is made of the following raw materials: 70kg of ethylene-vinyl acetate copolymer, 30kg of metallocene polyethylene, 15kg of maleic anhydride grafted polyethylene, 3kg of triglycidyl isocyanurate, 5kg of organic modified boron fiber, 2kg of lubricant, 2kg of antioxidant, and 80kg of flame retardant.
[0074] Moreover, among the raw materials of low-smoke halogen-free flame-retardant polyolefin materials, the mass content of vinyl acetate in ethylene-vinyl acetate copolymer is 18%, the melt index is 2.5g / 10min; the density of metallocene polyethylene is 0.94g / cm 3, a melt index of 1.2g / 10min; the maleic anhydride grafted polyethylene is maleic anhydride grafted polyethylene PE-g-MAH, and is selected from Guangdong Chuanheng New Material Technology Co., Ltd.; the organic modified boron fiber is prepared by the method of Preparation Example 1; the lubricant is ethylene bisstearamide and zinc stearate, and the weight ratio of ethylene bisstearamide and zinc stearate is 2:1; the antioxidant is antioxidant 1010 and antioxidant 168, and the weight ratio of antioxidant 1010 and antioxidant 168 is 1:2; the flame retardant is magnesium hydroxide and aluminum hydroxide, and the weight ratio of magnesium hydroxide and aluminum hydroxide is 1:2.
[0075] The low-smoke halogen-free flame-retardant polyolefin material is prepared by the following method: metallocene polyethylene, maleic anhydride grafted polyethylene, triglycidyl isocyanurate, lubricant, antioxidant, and flame retardant are added to ethylene-vinyl acetate copolymer, stirred for 2 minutes, and then organic modified boron fiber is added, stirred for 5 minutes, and a mixture is obtained. Then, a twin-screw extruder is used to extrude and granulate the mixture at a speed of 400r / min and an extrusion temperature of 160°C to obtain a low-smoke halogen-free flame-retardant polyolefin material.
[0076] Example 2
[0077] A low-smoke halogen-free flame-retardant cable for subways, which differs from Example 1 in that the raw material ratio of the low-smoke halogen-free flame-retardant polyolefin material used in the sheath layer is different.
[0078] Among them, the low-smoke halogen-free flame-retardant polyolefin material is made of the following raw materials: 60kg of ethylene-vinyl acetate copolymer, 40kg of metallocene polyethylene, 20kg of maleic anhydride grafted polyethylene, 4kg of triglycidyl isocyanurate, 4kg of organically modified boron fiber, 1kg of lubricant, 3kg of antioxidant, and 70kg of flame retardant.
[0079] Example 3
[0080] A low-smoke halogen-free flame-retardant cable for subways, which differs from Example 1 in that the raw material ratio of the low-smoke halogen-free flame-retardant polyolefin material used in the sheath layer is different.
[0081] Among them, the low-smoke halogen-free flame-retardant polyolefin material is made of the following raw materials: 80kg of ethylene-vinyl acetate copolymer, 20kg of metallocene polyethylene, 10kg of maleic anhydride grafted polyethylene, 2kg of triglycidyl isocyanurate, 6kg of organically modified boron fiber, 3kg of lubricant, 1kg of antioxidant, and 90kg of flame retardant.
[0082] Example 4
[0083] A low-smoke halogen-free flame-retardant cable for subways, which differs from Example 1 in that the raw material of the low-smoke halogen-free flame-retardant polyolefin material used in the sheath layer has a different source of organically modified boron fiber, and the organically modified boron fiber is prepared by the method of Preparation Example 2.
[0084] Example 5
[0085] A low-smoke halogen-free flame-retardant cable for subways, which differs from Example 1 in that the raw material of the low-smoke halogen-free flame-retardant polyolefin material used in the sheath layer has a different source of organically modified boron fiber, and the organically modified boron fiber is prepared by the method of Preparation Example 3.
[0086] Comparative Example
[0087] Comparative Example 1
[0088] A low-smoke halogen-free flame-retardant cable for subways, which differs from Example 1 in that an equal amount of boron fiber is used to replace the organic modified boron fiber in the raw material of the low-smoke halogen-free flame-retardant polyolefin material used for the sheath layer.
[0089] Comparative Example 2
[0090] A low-smoke halogen-free flame-retardant cable for subways, which differs from Example 1 in that the raw material of the low-smoke halogen-free flame-retardant polyolefin material used in the sheath layer and the steps T2-T3 in the preparation method of the organically modified boron fiber are different.
[0091] Steps T2-T3 are as follows: adding the pretreated boron fiber obtained in step T1 to 100 kg of water at a rotation speed of 300 r / min, stirring for 5 min, adding 7 kg of 3-(methacryloyloxy)propyltrimethoxysilane, stirring for 3 h, filtering, washing, and drying to obtain organically modified boron fiber.
[0092] In the washing process, the mixture was washed once with 30 kg of ethanol, then washed once with 30 kg of ethanol aqueous solution with a mass concentration of 30%, and then washed once with 30 kg of water to complete the washing process.
[0093] Comparative Example 3
[0094] A low-smoke halogen-free flame-retardant cable for subways, which differs from Example 1 in that, in the raw material of the low-smoke halogen-free flame-retardant polyolefin material used in the sheath layer, in the preparation method of the organic modified boron fiber, in step T3, an equal amount of triallyl isocyanurate is used to replace diethylene glycol monoallyl ether and sucrose oleate.
[0095] Comparative Example 4
[0096] A low-smoke halogen-free flame-retardant cable for subways, which differs from Example 1 in that in the raw material of the low-smoke halogen-free flame-retardant polyolefin material used in the sheath layer, in the preparation method of the organic modified boron fiber, in step T3, an equal amount of diethylene glycol monoallyl ether is used to replace triallyl isocyanurate and sucrose oleate.
[0097] Comparative Example 5
[0098] A low-smoke halogen-free flame-retardant cable for subways, which differs from Example 1 in that in the raw material of the low-smoke halogen-free flame-retardant polyolefin material used in the sheath layer, in the preparation method of the organic modified boron fiber, in step T3, an equal amount of sucrose oleate is used to replace triallyl isocyanurate and diethylene glycol monoallyl ether.
[0099] Comparative Example 6
[0100] A low-smoke halogen-free flame-retardant cable for subway, which is different from Example 1 in that the raw material of the low-smoke halogen-free flame-retardant polyolefin material used in the sheath layer is replaced by an equal amount of silicon dioxide to replace the organic modified boron fiber, and the average particle size of the silicon dioxide is 150 μm and the BET specific surface area is 90 m 2 / g.
[0101] Comparative Example 7
[0102] A low-smoke halogen-free flame-retardant cable for subways, which differs from Example 1 in that an equal amount of organically modified silicon dioxide is used to replace organically modified boron fiber in the raw material of the low-smoke halogen-free flame-retardant polyolefin material used for the sheath layer.
[0103] Organic modified silica was prepared by the following method:
[0104] T1. Add 5 kg of sodium hydroxide to 50 kg of water at a rotation speed of 300 r / min, stir for 5 min. Add 10 kg of silicon dioxide, stir for 2 h, filter, and obtain pretreated silicon dioxide.
[0105] The average particle size of silica is 150 μm and the BET specific surface area is 90 m 2 / g.
[0106] T2. Add the pretreated silica obtained in step T1 to 100 kg of water at a rotation speed of 300 r / min, and stir for 5 min. Add 2 kg of 3-(methacryloyloxy)propyltrimethoxysilane, stir for 3 h, and filter to obtain a grafted silica intermediate.
[0107] T3. Add 30 kg of toluene to 70 kg of isopropanol at a speed of 300 r / min and stir for 5 min. Add the grafted silica intermediate obtained in step T2 and stir for 5 min. Add 1 kg of triallyl isocyanurate, 2 kg of diethylene glycol monoallyl ether, and 2 kg of sucrose oleate and stir for 5 min. Add 0.1 kg of an organic initiator and stir for 3 h, filter, wash, and dry to obtain organically modified silica.
[0108] Among them, the organic initiator is benzoyl peroxide; in the washing treatment, it is washed once with 30 kg of ethanol, then washed once with 30 kg of ethanol aqueous solution with a mass concentration of 30%, and then washed once with 30 kg of water to complete the washing treatment.
[0109] Performance Testing
[0110] (1) The low-smoke halogen-free flame-retardant polyolefin materials obtained in Examples 1-5 and Comparative Examples 1-7 were respectively taken, and the following performance tests were performed on the low-smoke halogen-free flame-retardant polyolefin materials. The test results are shown in Table 1.
[0111] Among them, the tensile strength of low-smoke halogen-free flame-retardant polyolefin materials was tested in accordance with GB / T1040.1-2008 "Determination of tensile properties of plastics Part 1: General principles".
[0112] According to GB / T 1843-2008 “Determination of Izod Impact Strength of Plastics”, the notched impact strength of low-smoke halogen-free flame-retardant polyolefin materials is tested.
[0113] According to GB / T2406-2009 "Determination of Combustion Behavior of Plastics by Oxygen Index Method", the limiting oxygen index of low-smoke halogen-free flame-retardant polyolefin materials is tested.
[0114] Table 1 Test results
[0115]
[0116] As can be seen from Table 1, the low-smoke halogen-free flame-retardant polyolefin material of the present application has higher tensile strength and notched impact strength, with a tensile strength of 27.32-28.96 MPa and a notched impact strength of 21.72-23.25 kJ / m 2 , showing the advantages of high tensile strength and high notched impact strength. It also has a higher limiting oxygen index of 35.1-35.6%, showing high flame retardancy, meeting market demand.
[0117] Comparative Examples 1-2 are compared. Boron fiber is added to the raw material of the low-smoke halogen-free flame-retardant polyolefin material of Comparative Example 1; organic modified boron fiber is added to the raw material of the low-smoke halogen-free flame-retardant polyolefin material of Comparative Example 2, which is obtained by treating the boron fiber with 3-(methacryloyloxy)propyltrimethoxysilane. It can be seen that grafting organic matter on the surface of the boron fiber and modifying the boron fiber with organic matter can improve the dispersibility and compatibility of the boron fiber, and improve the tensile strength, notched impact strength and limiting oxygen index of the low-smoke halogen-free flame-retardant polyolefin material.
[0118] Comparative Examples 2-5 and Example 1 are compared. The organically modified boron fiber of Comparative Example 2 is obtained by treating the boron fiber with 3-(methacryloyloxy)propyltrimethoxysilane; the organically modified boron fiber of Comparative Example 3 is obtained by treating the boron fiber with 3-(methacryloyloxy)propyltrimethoxysilane and triallyl isocyanurate; the organically modified boron fiber of Comparative Example 4 is obtained by treating the boron fiber with 3-(methacryloyloxy)propyltrimethoxysilane and diethylene glycol monoallyl ether; the organically modified boron fiber of Comparative Example 5 is obtained by treating the boron fiber with 3-(methacryloyloxy)propyltrimethoxysilane and sucrose oleate; the organically modified boron fiber of Example 1 is obtained by treating the boron fiber with 3-(methacryloyloxy)propyltrimethoxysilane, triallyl isocyanurate, diethylene glycol monoallyl ether, and sucrose oleate. It can be seen that the organic modified boron fiber obtained by grafting different organic substances on the surface of the boron fiber has different effects in the low-smoke halogen-free flame-retardant polyolefin material. In addition, on the basis of grafting 3-(methacryloyloxy)propyltrimethoxysilane on the surface of the boron fiber and introducing siloxy and ester groups, triallyl isocyanurate, diethylene glycol monoallyl ether, and sucrose oleate are further grafted at the same time, introducing isocyanurate, ether, and hydroxyl groups, and increasing the number of side chains. By using the mutual cooperation between them, the tensile strength, notched impact strength, and flame retardancy of the low-smoke halogen-free flame-retardant polyolefin material are further improved, and the organic modified boron fiber shows a better use effect.
[0119] Comparison is made between Comparative Example 1 and Comparative Example 6. Boron fiber is added to the raw material of the low-smoke halogen-free flame-retardant polyolefin material of Comparative Example 1; silica is added to the raw material of the low-smoke halogen-free flame-retardant polyolefin material of Comparative Example 6. It can be seen that compared with adding silica to the raw material, adding boron fiber to the raw material and utilizing boron fiber to enhance the stability of the network structure of the low-smoke halogen-free flame-retardant polyolefin material and improve the cross-linking density can make the low-smoke halogen-free flame-retardant polyolefin material exhibit better tensile strength, notched impact strength and flame retardancy. Combined with Comparative Example 7 and Example 1. Organically modified silica is added to the raw material of the low-smoke halogen-free flame-retardant polyolefin material of Comparative Example 7; organically modified boron fiber is added to the raw material of the low-smoke halogen-free flame-retardant polyolefin material of Example 1. It can be seen that compared with the use of organic matter to graft silica, the use of organic matter to graft boron fiber is beneficial to improving the overall performance of the low-smoke halogen-free flame-retardant polyolefin material.
[0120] It should be noted that the embodiments described above are only used to explain the present application and do not constitute any limitation to the present application. The present application is described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present application may be modified as specified within the scope of the claims of the present application, and the present invention may be revised without departing from the scope and spirit of the present application. Although the present application described therein relates to specific methods, materials and embodiments, it does not mean that the present application is limited to the specific examples disclosed therein. On the contrary, the present application can be extended to all other methods and applications with the same functions.
Claims
1. Low smoke halogen-free flame retardant cable for subway, characterized by: The low-smoke halogen-free flame-retardant cable comprises a plurality of cable cores (1), the outer circumference of the plurality of cable cores (1) is provided with a wrapping layer (2), a filler (3) is provided between the wrapping layer (2) and the cable core (1), and the outer circumference of the wrapping layer (2) is provided with an inner protective layer (4), a ceramic silicone layer (5), a metal braided layer (6), and a sheath layer (7) in sequence from the inside to the outside; the sheath layer (7) is made of a low-smoke halogen-free flame-retardant polyolefin material; The low-smoke halogen-free flame-retardant polyolefin material is mainly made of the following raw materials in parts by weight: 60-80 parts of ethylene-vinyl acetate copolymer, 20-40 parts of metallocene polyethylene, 10-20 parts of maleic anhydride grafted polyethylene, 2-4 parts of triglycidyl isocyanurate, 4-6 parts of organically modified boron fiber, 1-3 parts of lubricant, 1-3 parts of antioxidant, and 70-90 parts of flame retardant; the organically modified boron fiber is obtained by treating boron fiber with 3-(methacryloyloxy)propyltrimethoxysilane, triallyl isocyanurate, diethylene glycol monoallyl ether, and sucrose oleate; The organic modified boron fiber is prepared by the following method: T1. Mix water and sodium hydroxide, add boron fiber, stir for 1-3 hours, filter, and obtain pretreated boron fiber; T2, mixing water and pretreated boron fiber, adding 3-(methacryloyloxy)propyltrimethoxysilane, stirring for 2-4 hours, filtering, and obtaining a grafted boron fiber intermediate; T3, mixing isopropanol and toluene, adding the grafted boron fiber intermediate, adding triallyl isocyanurate, diethylene glycol monoallyl ether, and sucrose oleate, adding an organic initiator, stirring for 2-4 hours, filtering, washing, and drying to obtain organically modified boron fiber; The weight ratio of the boron fiber, 3-(methacryloyloxy)propyltrimethoxysilane, triallyl isocyanurate, diethylene glycol monoallyl ether, and sucrose oleate is (9-11):(1-3):(0.5-1.5):(1-3):(1-3).
2. The low-smoke halogen-free flame-retardant cable for subway according to claim 1, characterized in that: The organic initiator is one or more of benzoyl peroxide, tert-butyl perbenzoate, cumene hydroperoxide, and tert-butyl hydroperoxide.
3. The low-smoke halogen-free flame-retardant cable for subway according to claim 1, characterized in that: The boron fiber has an average diameter of 30-300 μm and an average length of 1-5 mm.
4. The low-smoke halogen-free flame-retardant cable for subway according to claim 1, characterized in that: The lubricant is one or more of stearic acid, zinc stearate, stearic acid amide, and ethylene bis stearic acid amide.
5. The low-smoke halogen-free flame-retardant cable for subway according to claim 1, characterized in that: The antioxidant is one or more of antioxidant 1010, antioxidant 1076, antioxidant 2246, antioxidant 168, and antioxidant TH-412S.
6. The low-smoke halogen-free flame-retardant cable for subway according to claim 1, characterized in that: The flame retardant is one or more of magnesium hydroxide, aluminum hydroxide and zinc borate.
7. The low-smoke halogen-free flame-retardant cable for subway according to claim 1, characterized in that: The low-smoke halogen-free flame-retardant polyolefin material is prepared by the following method: Ethylene-vinyl acetate copolymer, metallocene polyethylene, maleic anhydride grafted polyethylene, triglycidyl isocyanurate, organic modified boron fiber, lubricant, antioxidant and flame retardant are mixed and extruded into granules to obtain low-smoke halogen-free flame retardant polyolefin material.
8. The low-smoke halogen-free flame-retardant cable for subway according to claim 7, characterized in that: In the extrusion granulation process, a twin-screw extruder is used with an extrusion temperature of 150-170°C and a rotation speed of 300-500r / min.
Citation Information
Patent Citations
Cracking-resistant thermoplastic low-smoke halogen-free flame-retardant polyolefin cable material
CN103030917A
Low-smoke halogen-free flame-retardant cable and processing technology thereof
CN117089133A